2020
DOI: 10.1021/acs.joc.9b02946
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Strong Acidity Enhancing the Effect in Protic Ionic Liquids Quantified by Equilibrium Acidity Studies: A Crucial Role of Cation Structures on Dictating the Solvation Properties

Abstract: The equilibrium acidities for several series of structural and electronic different organic acids were measured in 3-pyrrolidinium-based aprotic and protic ionic liquid (IL) analogues, that is, [Bmpy]­[NTf2], [BpyH]­[NTf2], and [PyH2]­[NTf2], by the UV–Vis method. The acidities of neutral acids are found to be much stronger in the protic ILs (PILs) than aprotic ILs (AILs), and the acidifying effect in the two PILs roughly increases proportionally to the number of protons in the cation of the PIL. On the other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…The commonly seen and widely used DES composed of a 1:2 molar ratio of choline chloride to ethylene glycol (abbreviated as [Ch]­[Cl]:2EG) was taken as the representative medium for the acidity determination in this work. The p K a values were obtained by an ultraviolet–visible (UV–Vis)-based approach, which has been introduced for the acidity determination in ILs and also is specified in the Experimental Section and in Sections S1.3 and S1.4 of the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The commonly seen and widely used DES composed of a 1:2 molar ratio of choline chloride to ethylene glycol (abbreviated as [Ch]­[Cl]:2EG) was taken as the representative medium for the acidity determination in this work. The p K a values were obtained by an ultraviolet–visible (UV–Vis)-based approach, which has been introduced for the acidity determination in ILs and also is specified in the Experimental Section and in Sections S1.3 and S1.4 of the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…Systematic study of equilibrium acidities (p K a , the negative logarithm of the acid dissociation constant K a ) in solution has been proven to be a convenient and effective approach for detecting subtle solvation behaviors of solvents. In this regard, previously, a large number of acidity scales for different Brönsted acids in various molecular and ionic solvents have been established. Through the acidity comparisons and correlations between solvents, several distinct solvation behaviors between molecular solvents and ionic media thus have been explicitly revealed. , In the past few years, although there have been several acidity investigations in a number of commonly seen DESs, most of these reports were focused on the relative acidities of DESs themselves in molecular solvents. There is practically no investigation on the acidities for a relatively wide range of organic acids with various structures and electronic properties in neat DES systems. It is worth noting that Abbott and co-workers first reported acidities in several choline-based DESs; however, their work was mainly focused on a series of carboxylic acids (COO–H acids), with no report on the acidity determination of other types of organic compounds, such as C–H, O–H, and N–H acids.…”
Section: Introductionmentioning
confidence: 99%
“…Although, in practice, a metathesis reaction with salt exchange has been proven to be a more controlled way of obtaining PILs, for all intents and purposes and for the sake of the following discussion, we shall think of them as stemming from a simple acid/base reaction: where the proton moves from the acid onto the base, forming two molecular ions. A prototypical example of this reaction is the formation of ethylammonium nitrate which, incidentally, is one of the first ILs ever discovered…”
Section: Introductionmentioning
confidence: 99%
“…One of the most and readily available indicators of these propensities is the aqueous p K a . Unfortunately, the p K a depends strongly on the dielectric properties of water and on its solvation ability toward the ionized forms in the right-hand side of reaction , and its application in the context of PILs is not entirely justified . Nevertheless, it has been found that a very large difference in p K a (Δp K a ) between AH and BH + (greater than 10 units) generally indicates the formation of a completely ionized medium. , In all other cases, however, the fate of reaction is very difficult to predict from p K a .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation